Selection signatures in the CIMMYT International Elite Spring and Semi-arid Wheat Yield Trials - Mondaini, Alexandre; Rosyara, Umesh; Sehgal, Deepmala; Dreisigacker, Susanne (Wiley, 2022)
The International Maize and Wheat Improvement Center (CIMMYT) annually distributes advanced wheat (Triticum aestivum L.) breeding lines to collaborators worldwide through the International Wheat Improvement Network. Lines are disseminated through international nurseries, including the Elite Spring Wheat Yield Trial (ESWYT) targeted to optimal (irrigated and high production) wheat production areas and the Semi-arid Wheat Yield Trial (SAWYT) targeted to low rainfall environments. A total of 2,184 wheat lines that formed the ESWYT and SAWYT since 1979 and 1992, respectively, were genotyped using genotyping-by-sequencing to explore trends of genetic diversity and selection footprints associated with continuous crop improvement and adaptation. Due to a small population size of each trial, adjacent year trials were pooled into subpopulations. Population structure was evaluated using discriminant analysis of principal components and fixation index. High levels of admixture within and across the ESWYT and SAWYT subpopulations were revealed, indicating that the entire genetic diversity in the overall CIMMYT germplasm pool is harnessed to target core traits to individual mega-environments. Genome wide scans of deviations of minor allele frequencies at each marker identified large linkage blocks in several chromosomes. The scans also revealed that 9.8 and 2.0% of the SNP markers could be associated to selection signatures over time and to environmental adaptation (significant deviations between ESWYT and SAWYT), respectively. Several known genes and previously identified haplotypes associated with grain yield in more recent CIMMYT elite germplasm did fall into genomic regions with directional selection.